Investigation of lipid-lowering mechanism of Tamarindus indica fruit pulp in HepG2 cells using proteomic and transcriptomic approaches / Ursula Chong Rho Wan - Chong, Ursula Rho Wan (2014)
Tamarindus indica (T. indica), or tamarind, is an edible fruit widely used in many applications including culinary, industrial, and medicinal purposes. It has been shown to exhibit hypolipidaemic effects in hamsters and humans. Previous studies have also shown that the methanol extract of T. indica fruit pulp regulated genes related to lipid metabolism. However, the lipid-lowering mechanism of the fruit has not been fully understood. The objective of this present study is to determine the lipid-lowering mechanism of T. indica fruit pulp using proteomic and transcriptomic approaches. Proteomic analyses were first performed to formulate a hypothesis on the hypolipidaemic action of the fruit. When secreted proteins extracted from control and T. indica fruit-treated HepG2 cells were subjected to 2-dimensional gel electrophoresis, the expression of seven proteins was found to be significantly different (p < 0.03125). As for the HepG2 cell lysate proteins, 20 spots were found to be significantly altered (p < 0.05). Fourteen spots were identified and categorised based on their biological functions, namely the oxidative phosphorylation, metabolism, protein biosynthesis, cell proliferation and differentiation and mRNA splicing. When the altered secreted proteins and cell lysate proteins were co-analysed using Ingenuity Pathway Analysis (IPA) software, lipid metabolism was found to be the top network being regulated, with a score of 31. Further data mining of the proteomic data as well as previously obtained microarray data indicated that the fruit pulp extract modulates its lipid-lowering effect through the activation of PPARα. To further demonstrate the hypolipidaemic effect of the fruit, lipid studies were conducted. DNA microarray analyses were also conducted to elucidate its mechanism of action, and fenofibrate, a hypolipidaemic drug which is a ligand to PPARα, was used as a comparison to T. indica fruit which was hypothesised to lower lipids in a similar mode of action. HepG2 cells were first treated with 0.3 mM palmitic acid to induce hepatic steatosis. The lipid loaded-cells were then treated with different concentrations of T. indica fruit pulp extract and the total triglyceride and cholesterol levels were measured. Total cellular RNA was then extracted for DNA microarray analysis and the significantly regulated genes were subjected to IPA software analysis. Results showed that treatment with 0.1 mg/ml T. indica fruit pulp extract reduced total triglyceride and total cholesterol by 40 % and 18 % respectively, a level comparable to fenofibrate. DNA microarray analyses showed that treatment of lipid loaded-HepG2 cells with the same concentration of T. indica fruit extract regulated 140 genes (p < 0.05) when compared to control. Further data mining using IPA analysis showed that 21 genes were involved in lipid metabolism network and PPARα and PPARγ activation could be responsible for the lipid-lowering effects, possibly attributed to proanthocyanidins, the major polyphenol found in T. indica fruit extract. As a conclusion, the methanol extract of T. indica fruit pulp lowers lipid levels significantly, particularly triglyceride and it does so through the activation of PPARα, a mechanism similar to fenofibrate.